The Influence of Economic Value, Perceived Ease of Use, Social Influence, Company Reputation, Features and Rewards on The Intention to Use the OLLIN Application - Budisetiawati, Ardiva; Thabrani, Gesit (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study examines the influence of economic value, perceived ease of use, social influence, company reputation, features, and rewards on the intention to use the OLLIN application by Bank Nagari among Generation Y and Z in Padang City. A quantitative approach was employed, utilizing purposive sampling of 176 respondents, and the data were analyzed using Partial Least Squares and SmartPLS 4.0. The findings indicate that several variables have a significant positive influence on the intention to use the app, namely economic value, company reputation, and awards. These results suggest that Bank Nagari should focus on enhancing economic value, ease of use, reputation, and innovative features to increase app adoption among younger generations. This study provides practical implications for Bank Nagari, which aims to attract the attention and increase the loyalty of Generation Y and Z users in Padang City, while strengthening its competitive position in the growing digital banking industry.